Estimation of structure , optical and Electrical properties of novel CuInSex nanoparticles Vi Hydrothermal method - Aryan A. Omer, Mohanad Q.Kareem, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, CuInSe nanoparticles were effectively produced using the nanometric technique in this study. The XRD diffraction results showed that it has a monoclinic structure and a hexagonal phase. The expansion of the XRD line of CuInSe is due to the small crystal size. However, with a large number of grid ratios determined by the comparison. The FESEM images confirmed the Se configurations of the agglomerated and circular rectangular nanoparticles. According to the optical properties, it is found that the best energy gap is eV. 1.25 ev ... which helps the thermoelectric performance of materials or sorbents in solar cell applications.